Bacterial Multidrug Efflux Pumps at the Frontline of Antimicrobial Resistance: An Overview - Lulu Huang (Antibiotics, 2022)
Multidrug efflux pumps function at the frontline to protect bacteria against antimicrobials by decreasing the intracellular concentration of drugs. This protective barrier consists of a series of transporter proteins, which are located in the bacterial cell membrane and periplasm and remove diverse extraneous substrates, including antimicrobials, organic solvents, toxic heavy metals, etc., from bacterial cells. This review systematically and comprehensively summarizes the functions of multiple efflux pumps families and discusses their potential applications. The biological functions of efflux pumps including their promotion of multidrug resistance, biofilm formation, quorum sensing, and survival and pathogenicity of bacteria are elucidated. The potential applications of efflux pump-related genes/proteins for the detection of antibiotic residues and antimicrobial resistance are also analyzed. Last but not least, efflux pump inhibitors, especially those of plant origin, are discussed.